Balancing the antibacterial and osteogenic effects of double-layer TiO2 nanotubes loaded with silver nanoparticles for the osseointegration of implants. Issue 6 (24th January 2023) - Sun, Lei; Chen, Xuzhuo; Chen, Ruiguo; Ji, Zhibo; Mu, Haizhang; Liu, Chun; Yu, Jinlan; Wang, Jiarong; Xia, Rong; Zhang, Shanyong; Xu, Yin; Ma, Kun; et al.
Abstract : The improvement of Ag nanoparticles includes not only the antibacterial effect but also balancing the side effects from the antibacterial effect and osteogenesis properties, which can lead to an increased success rate of titanium implants. Abstract : The improvement of Ag nanoparticles (AgNPs), in particular, loaded titania nanotubes, includes not only the antibacterial effect but also balancing the side effects from the antibacterial effect and osteogenesis properties, which can lead to an increased success rate of implants. Herein, based on the various needs of the graft to inhibit bacteria at different stages in vivo, we used a special osteogenic honeycomb-like "large tube over small tube" double-layered nanotube structure and created ultra-small-sized silver nanoparticles uniformly loaded on the surface and the interior of double-layer nanotubes by an optimized sputter coating method to ensure the time-dependent controllable release of antibacterial Ag ions from grafts and achieve the balance of the antibacterial effect and osteogenesis properties. The release of Ag + from DNT-Ag8 was determined by inductively coupled plasma spectrometry. The release rate of Ag was slow; it was 30% on the first day and plateaued by the 19th day. Porphyromonas gingivalis adhesion and live bacteria were less abundant on the surface of DNT-Ag8, reaching an antibacterial efficiency of 55.6% in vitro . DNT-Ag8 shows a significantly higher antibacterial effect in a rat model infected with Staphylococcus aureus . An in vitro study demonstrated that DNT-Ag8 had no adverse effects on the adhesion, viability, proliferation, ALP staining, or activity assays of rat BMSCs. In contrast, it increased the expression of osteogenic genes. In vivo, DNT-Ag8 promoted bone–implant osseointegration in a beagle mandibular tooth loss model. This study demonstrated that the uniform loading of small-diameter silver nanoparticles using a honeycomb bilayer nanotube template structure is a promising method for modifying titanium surfaces to improve both bacteriostasis and osseointegration.